Investigation of gastrintestinal parasites in rabbits of the species Oryctolagus cuniculus in the Northwest region of São Paulo, Brazil (Research, Society and Development, 2021)
Enteroparasites can be pathogenic for the rabbit population and for this reason, we have investigated its occurrence in bioterium of rabbits. The sample group was composed of 103 adult males of the species Oryctolagus cuniculus and New Zealand breed. Fecal samples (n = 103) were processed using the Willis Techniques (Fluctuation in saturated sodium chloride solution with specific density of 1.20 g/mL) and Faust (Centrifugal-flotation in zinc sulphate with density of 1.18 g/ml). The diameters of larger and smaller sizes of the sporocysts and sporozoites of the coccidia were measured by means of optical microscopy using the program CellSens 1.17_00_en_Rhine_13Feb2017. The Faust Technique showed positivity of 39.74% (31/78) for Eimeria spp, while in Willis Technique, 35.90% (28/78) was observed for Eimeria spp, being the species Eimeria perforans and in 51.28% (47/78) of them there was no parasitism. We identified, for the first time, the occurrence of the specie E. perforans in rabbits of the species O. cuniculus, New Zealand breed kept in a bioterium. Therefore, it is extremely important for the implantation of parasitic control of rabbits kept in bioterium for scientific purposes, the monitoring of possible infections by means of periodic coproparasitological exams.